Use of supplemental oxygen in emergency patients: a systematic review and recommendations for military clinical practice. Issue 6 (15th December 2018) - Cottey, Laura; Jefferys, S; Woolley, T; Smith, J E
Abstract : Introduction: Supplemental oxygen is a key element of emergency treatment algorithms. However, in the operational environment, oxygen supply poses a challenge. The lack of high-quality evidence alongside emerging technologies provides the opportunity to challenge current guidelines. The aim of this review was to appraise the evidence for the administration of oxygen in emergency patients and give recommendations for its use in clinical practice. Methods: A critical review of the literature was undertaken to determine the evidence for emergency supplemental oxygen use. Results: Based on interpretation of the limited available evidence, five key recommendations are made: pulse oximetry should be continuous and initiated as early as possible; oxygen should be available to all trauma and medical patients in the forward operating environment; if peripheral oxygen saturations (SpO2 ) are greater than or equal to 92%, supplemental oxygen is not routinely required; if SpO2 is less than 92%, supplemental oxygen should be titrated to achieve an SpO2 of greater than 92%; and if flow rates of greater than 5 L/min are required, then urgent evacuation and critical care support should be requested. Conclusion: Oxygen is not universally required for all patients. Current guidelines aim to prevent hypoxia but with potentially conservative limits. Oxygen should be administered to maintain SpO2 at 92% or above. New areas for research, highlighted in this review, may provide a future approach for oxygen use from point of injury to definitive care.